Magnitude, temporal trend and inequality in burden of neck pain: an analysis of the Global Burden of Disease Study 2019 - Fengshuo Xu; Xiangdong Zhang; Meng Yang; Qi Zhao; Qiusheng Wang; Jie Lian; Rong Zhang; Tianyun Chu; Zhaoxi Kou; Mingyu Zhao (BMC Musculoskeletal Disorders)
Abstract Background This study aimed to comprehensively assess the magnitude, temporal trends, and inequalities associated with socioeconomic development in neck pain (NP) based on the Global Burden of Disease Study 2019. Methods An assessment of incidence and years of life with disability (YLD) at the global, regional, and country levels by age, sex and year was conducted for NP. Joinpoint regression (JPR) was used to analyze trends between 1990 and 2019. Decomposition analysis was used to explore the extent to which population growth, aging, and epidemiological changes influenced the changes in incidence and YLD. A Bayesian Age-Period-Cohort (BAPC) model was constructed to predict trends over the next 25 years. Concentration curve and concentration index were used to examine the cross-country relative inequality of the burden of NP at the socio-demographic index (SDI) level. Results In 2019, the global ASIR and ASDR of NP were 579.085 and 267.348 per 100,000 individuals, respectively. JPR analysis showed that the global ASIR and ASDR have decreased slightly over the past 30 years, although an increase was observed between 2011 and 2019. The BAPC model predicted that this upward trend would continue over the next 25 years. Decomposition analysis showed that the global increase in incidence and YLD in 2019 compared to 1990 was mainly driven by population growth. The burden of NP was higher in the middle-aged, old-age, and female groups, with differences in regional distribution. The analysis of cross-country inequality showed that the burden of NP was disproportionately concentrated in countries with a high SDI, and this phenomenon continued to increase over the 30-year study period. Conclusions Globally, NP remains an important public health problem, and governments are urgently required to raise public awareness about NP and its risk factors, implement targeted prevention and control policies, and deliver the necessary health services.